Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil - Fernandes, Camile Sorbo; Campos-Filho, Ivanklin Soares; Bichuette, Maria Elina (Zootaxa, 2018)
The new species Cylindroniscus platoi n. sp. is herein described. As far as known, the species occurs only in three caves developed in a continuous limestone outcrop at Pedro Leopoldo municipality, Minas Gerais State. Cylindroniscus platoi n. sp. is regarded as an endemic troglobite based on its limited distribution and on non-obvious troglomorphisms found on its body surface.